Błąd co do nierozerwalności małżeństwa (kan. 1099 KPK) w świetle wyroku Roty Rzymskiej c. Erlebach z dnia 9 lipca 1999 r. - Góralski, Wojciech (Ius Matrimoniale, 2017)
The case concerns the marriage between Marcin and Maria, who, after a three-year-long relationship, entered into marriage on 24 July 2984, after being granted a dispensation from an impediment to marriage (the bridegroom-to-be was not christened). At first marriage, the fruit of which was a child, was happy, but in August 1992 it was broken by wife. Marcin brought the case before the Tribunal C. to have the marriage declared null and void, citing numerous reasons for nullity. The Tribunal determined the matter on 24 March 1995 concerning two reasons: Maria’s total simulation of marriage consent and Marcin’s error regarding the indissolubility of marriage. The parties, complainant’s three witnesses and one witness called ex officio (a priest who prepared the parties for marriage) were examined during evidentiary instruction and then, on 30 I 1996, the Tribunal passed a negative sentence regarding both reasons for nullity. After the complainant appealed to K. Tribunal (Tribunal of Second Instance) on 3 September 1997, a negative sentence was passed regarding simulation, but a positive sentence was passed regarding the indissolubility of marriage. Pursuant to canon 1682 § 1 of the Code of Canon Law, the matter was transmitted to the third instance, namely the Roman Rota, where a negative sentence was passed on 9 July 1999. In the commentary on Rotal sentence, the author highlights the fact that the judges were able to demonstrate skillfully that Marcin’s error did not determine his will.